Engineered endothelium-mimicking antithrombotic surfaces via combination of nitric oxide-generation with fibrinolysis strategies - Wenxuan Wang; Qing Ma; Da Li; Wentai Zhang; Zhilu Yang; Wenjie Tian; Nan Huang (Bioactive Materials)
Thrombosis associated with implants can severely impact therapeutic outcomes and lead to increased morbidity and mortality. Thus, developing blood-contacting materials with superior anticoagulant properties is essential to prevent and mitigate device-related thrombosis. Herein, we propose a novel single-molecule multi-functional strategy for creating blood-compatible surfaces. The synthesized azide-modified Cu-DOTA-(Lys)3 molecule, which possesses both NO release and fibrinolysis functions, was immobilized on material surfaces via click chemistry. Due to the specificity, rapidity, and completeness of click chemistry, the firmly grafted Cu-DOTA-(Lys)3 endows the modified material with excellent antithrombotic properties of vascular endothelium and thrombolytic properties of fibrinolytic system. This surface effectively prevented thrombus formation in both in vitro and in vivo experiments, owing to the synergistic effect of anticoagulation and thrombolysis. Moreover, the modified material maintained its functional efficacy after one month of PBS immersion, demonstrating excellent stability. Overall, this single-molecule multifunctional strategy may become a promising surface engineering technique for blood-contacting materials.